Fraseologia diacrònica: «Vengut és qui us gratarà la tinya» (Curial e Güelfa). - MARTINES, JOSEP (Scripta)
This article explores a methodological approach to research on the phraseological component in diachrony. This approach is based on diachronic semantics and lexicology, on cultural history and on the use of digitised corpora, data provided by geolinguistics and contrastive linguistics. It focuses on the study of the origin of the locution «Gratar la tinya a algú» 'to hit someone'. It shows the possible Italian origin of this phraseological unit, first documented in the Curial e Güelfa and also present in Andreu Febrer's translation of Dant's Commedia. This has made it necessary to analyse the history, on the one hand, of the verb gratar in Catalan and the phraseology it has generated and, on the other, of the Italian locution «Grattare la tigna a qualcuno». It also shows how this locution must have spread in Catalan from diachronic dictionaries to some contemporary dictionaries and phraseological inventories and current literary texts.